Association of Postnatal growth with birth weight, gestational age, sex and intrauterine growth in very low birth weight Infants - chandran, Rabindran; Parakh, Hemant; J K, Ramesh; Reddy, Prashant (International Journal of Medical Research and Review, 2015)
Introduction: The postnatal growth pattern is dependent on many biological factors. Objective: To analyse the effect of birth weight, gestational age, sex and intrauterine growth on the postnatal growth pattern of VLBW babies. Methods: Retrospective case analysis of 129 neonates between January-2012 to December-2014. Weight was serially measured from birth till discharge and respective z scores were calculated as per data from Fenton’s 2013 references. Statistical Analysis: All data were collected in validated preformatted proforma sheet & analysed using appropriate statistical methods. Results: The mean birth weight & gestational age at birth were 1.292 kg & 32.24 weeks respectively. The mean z scores for weight at birth was -1.3989 which decreased to -2.1 by day 7. There was significant difference in gestation at birth & discharge and total duration of hospitalization based on birth weight. There was significant difference in gestation at birth & discharge and total duration of hospitalization, lowest weight, time to regain birth weight & day 1 & day 7 z scores based on gestation. Though SGA infants had more weight loss initially, they exhibited desired catch up growth during hospital stay and time to regain birth weight & total days of hospitalization were significantly less. Conclusion: Gestation is the predominant determinant of growth pattern followed by birth weight. There is no significant difference in growth between male & female babies. SGA babies demonstrated significant catch up growth despite initial significant weight loss.